Formation Pattern State Defense Reserve Components In Five Countries Of Asean - Bayu Setiawan (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
This research is a qualitative research, which aims to describe the ideal pattern for Indonesia in building the reserve component base on the result of benchmarking and review of the formation pattern of the Asean countries, namely Indonesia, Malaysia, Singapore, the Phlilipines, and Thailand. The place of research were Directorate of Reserve Component and the Directorate of State Defense of Defense Potential, Directorate General of Defense Potentioal, Ministry of Defence of the Republic of Indonesia, Commission I of the House of Representatives, and the Defence Attache of the five Asean countries. The data was collected by using Focus Group Discussion method, questionnaries, interviews, direct observation, and document verification. Data analysis was perfomed using a model of the Analytical Hierarchy Process (AHP) Thomas L. Saaty, such as, to determine actor, pattern, and actor with the highest priority and become the most important criteria in the formation of national defense reserve component in five Asian countries. Result of research on the highest priority and the most important criteria: (1) for Factor: Deterrent Power; (2) for Pattern: Budgeting; and (3) for Actor: the Thailand Kingdom. In this study we analyzed the implementation of eight key competences of Michael Zwell, ie, beliefs and values, skills, experience, personality traits, motivation, control emotional issues, intellectual ability, and the culture of the organization in six patterns for the formation of national defense reserve component in the Kingdom of Thailand, namely recruitment, training (development), use (utilities), closure, reward and punishment, and budgeting. The result of the analysis shows that the model and the development time in military basic training phase has the highest priority in improving the competence of members of the reserve component. In order to increase the deterrent power of the nation and country, Indonesia needs the competence of members of the reserve components that are national resources defense. Therefore, to improve the competence of defense reserve component member of the country, Indonesia needs to implement eight key competences of Michael Zwell into the military basic training curriculum, which is the part of a national programme to defend the country, and put the Ministry of Defence as a leading sector.